2014
DOI: 10.1371/journal.pone.0087730
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Multivalent Antifungal Peptides Effective against Fungi

Abstract: Taking advantage of the cluster effect observed in multivalent peptides, this work describes antifungal activity and possible mechanism of action of tetravalent peptide (B4010) which carries 4 copies of the sequence RGRKVVRR through a branched lysine core. B4010 displayed better antifungal properties than natamycin and amphotericin B. The peptide retained significant activity in the presence of monovalent/divalent cations, trypsin and serum and tear fluid. Moreover, B4010 is non-haemolytic and non-toxic to mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 59 publications
2
34
0
Order By: Relevance
“…Bacterial viability assay performed in parallel with the membrane potential dissipation assay further confirm that the loss of membrane potential is associated with bacterial lethality, thus demonstrating the membrane-targeting antimicrobial activity of the cationic polymers (Fig. S4c) [55][56][57][58][59]. Next, we examined the cytotoxicity of the polymers for the human telomerase-immortalized corneal epithelial cells (hTCEpi) by real time xCELLigence cell index (CI) impedance measurements.…”
Section: In Vitro Evaluation Of Membrane Selectivity Of Lpei and Bpeimentioning
confidence: 72%
“…Bacterial viability assay performed in parallel with the membrane potential dissipation assay further confirm that the loss of membrane potential is associated with bacterial lethality, thus demonstrating the membrane-targeting antimicrobial activity of the cationic polymers (Fig. S4c) [55][56][57][58][59]. Next, we examined the cytotoxicity of the polymers for the human telomerase-immortalized corneal epithelial cells (hTCEpi) by real time xCELLigence cell index (CI) impedance measurements.…”
Section: In Vitro Evaluation Of Membrane Selectivity Of Lpei and Bpeimentioning
confidence: 72%
“…Previous studies have indicated that incubation of the full-length peptide with trypsin generates a number of proteolytically processed fragments and a partial loss of antimicrobial activities in the presence of tear fluid (32). Since the microenvironment in the stroma encompasses a number of proteases, we sought to investigate the efficacy of the full-length SESB2V peptide and its various sequentially truncated variants.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, increase of activity is likely a consequence of the molar increase of physically linked AMP units per molecule of peptide, and not of any significant change in the mechanism of action. Increased antimicrobial activity was also associated with longer antifungal peptides in the case of the concatemer series of (RW) and (KW) dimeric peptides (Gopal et al 2012) or of a tetramer b r a n c h e d d e r i v a t i v e o f B 4 0 1 0 ( R G R K V V R R ) (Lakshminarayanan et al 2014), as well as in the antibacterial repeats of BP100 (Badosa et al 2013), although no mechanistic data were reported in these studies.…”
Section: Discussionmentioning
confidence: 99%